Comparison of Maternal and Perinatal Outcome Between 4 cm vs 6 cm Cervical Dilatation at Amniotomy - Tariq, Seema; yazdani, Tehreem (Pakistan Armed Forces Medical Journal, 2025)
ABSTRACT Objective: To compare maternal and perinatal outcome between 4 cm vs 6 cm cervical dilatation at Amniotomy among women undergoing induction of labor at our unit. Study Design: Comparative cross-sectional study. Place and Duration of Study: Obstetrics Department, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Oct to Dec 2022. Methodology: This study was conducted on women undergoing induction of labor at our unit. Women participating in this study were divided into two Groups. Group-I had Amniotomy at 4 cm of cervical dilatation while Group-II had Amniotomy at 6 cm of cervical dilatation. Both the Groups were followed up till the delivery for maternal outcome and 12 hours after the delivery for immediate peri-natal outcome. Maternal and perinatal outcomes observed in both Groups were compared for any significant difference. Results: A total of 634 women with mean age of 28.51±5.51 years meeting the criteria were recruited for this study. Two Groups were made for comparison. 321(50.6%) women had Amniotomy at 4 cm dilatation while 313(49.4%) had Amniotomy at 6 cm dilatation. Statistical analysis showed that when both the Groups were followed up, no statistically significant difference was recorded in any of the maternal or peri-natal outcome parameters included in this study (p-value>0.05). Conclusion: Induction of labor via Amniotomy could be done effectively both at 4 cm and 6 cm cervical dilatation. Both maternal and perinatal outcome parameters were not significantly different in women undergoing Amniotomy at these two different cervical dilatations in our study.